Reno duodenal fistula: A rare clinical presentation. - Estrugo, Roberto; Ruso, Luis; de Simone, Gustavo; Schenone, Héctor (Cirugía del Uruguay, 1988)
A case of sponteneous pyeloduodenal fistula, that provoked a gastroduodenal stenosis syndrome, is pre• sented.